gut health and serum growth hormone level of broiler chicken fed dietary chitin and chitosan from cricket and shrimp - Ibitoye, E. B.; Lokman, I. H.; M. N., M. Hezmee; Goh, Y. M.; A. B. Z., Zuki; Jimoh, A. A.; Danmaigoro, A.; Pilau, Nicholas N. (Elsevier BV, 2019)
Growth hormones (GH) alone does not explain the growth rate in the chicken as growth in an animal is multi-factorial. Normal morphology of the intestinal villus and crypt, with adequate regulation of intestinal nutrient transporters, is essential to a healthy gut. Nutrition plays a significant role in gut health management, but information on the effect of dietary chitin and chitosan on gut morphology, gene expression of nutrient transporter, and serum levels of GH in broiler chickens is scanty. Thus, this study aimed at evaluating the comparative effect of dietary chitin and chitosan from cricket and shrimp on the small intestinal morphology, relative gene expression of intestinal nutrient transporters and serum level of GH in the broiler. A total of 150 day-old male Cobb500 broiler chicks were randomly allotted to one of the five treatment groups (n = 30). Treatment 1 was fed basal diet only, treatments 2 to 5 were fed a basal diet with 0.5 g cricket chitin, cricket chitosan, shrimp chitin, and shrimp chitosan, respectively, per kg diet. At days 21 and 42, duodenal and jejunal samples were assessed for structural morphology and jejunum for the relative gene expression of PepT1, EAAT3, SGLT1, and SGLT5 using quantitative real-time PCR. Results bared that dietary cricket chitosan and shrimp chitosan significantly (P < 0.05) improved jejunal villus height and reduced crypt depth without improving the body weight (BW). The gut morphology of birds under cricket chitin was poor and significantly (P < 0.05) different from other treated groups. Both the dietary chitin and chitosan at day 21 and only dietary chitosan at day 42 significantly (P < 0.05) down-regulated the relative mRNA expression of PepT1, EAAT3, SGLT1, and SGLT5 of broiler chickens. Treated groups differ non-significantly at both phases, while cricket chitin numerically increased the relative expression of PepT1, EAAT3, and SGLT1. Therefore, the potential of cricket chitin to improve BW and to up-regulate nutrient transporters is worthy of further exploration.